Electromagnetic Compatibility (EMC) Ambient Measurement Effect from Rail Environments Towards Cardiac Pacemaker Immunity - Yaman, Mohamad Nor Izzuddin; Sapuan, Syarfa Zahirah (Evolution in Electrical and Electronic Engineering, 2021)
The purpose of this research is to investigate the impact of electromagnetic compatibility (EMC) ambient measurement on cardiac pacemaker immunity in train settings. When a railway station employs more electronics, the system's complexity increases as a result of interference and attenuation. External factors, such as train environments or the surrounding surroundings, may cause interference with an implanted device like as a pacemaker. To avoid this unintentional electromagnetic interference (EMI) effect, it is necessary to be aware of the possibility and take specific measures. Real measurements will be taken at the train station under various circumstances using loop and tri-log antennas, each of which must be linked to a spectrum analyzer. For analysis, the measurement data was compared to the pacemaker immunity level. This study shows that just one measurement failed out of 44, particularly at the Kepong Baru station in the V-N direction at the frequency 393.975 MHz. The test yielded a value of 111.86 dBµV/m, which is 2.39 dBµV/m over the pacemaker's allowed limit.